Artificial Intelligence—A Good Assistant to Multi-Modality Imaging in Managing Acute Coronary Syndrome - Liu, Ming-hao; Zhao, Chen; Wang, Shengfang; Jia, Haibo; Yu, Bo (Frontiers in Cardiovascular Medicine, 2022)
Acute coronary syndrome is the leading cause of cardiac death, which has great impact on patients prognosis. Early identification and proper management are the keys for better outcome, which has improved significantly with the development of various cardiovascular imaging modalities. Recently, artificial intelligence is growing to enhance the capability of cardiovascular imaging to perform more efficiently and make more accurate diagnosis and decision-making process. This review demonstrates recent application of AI in cardiovascular imaging to handle better patient care.